Routine Counseling Vs Comprehensive Counseling: Do they affect patient’s Satisfaction Level? - Dhakal, Sanjeeva (Journal of Nepalgunj Medical College, 2019)
Background: Communication with the patient is not just an add-on; it is the backbone where patient care rests. Effective communication is an important tool to develop good relationship with the patients. Objectives: The present study was undertaken to assess the difference in the satisfaction level of the patients after a “Routine counseling” and “Comprehensive counseling”. Materials and Method: It is hospital based comparative study. In this study one hundred patients admitted to the surgical ward of the Nepalgunj Medical College Teaching Hospital, Kohalpur were taken. These patients were divided into two groups. Group (A) which consist fifty patients, had a Routine counseling and group (B) consisting of another fifty patients had a Comprehensive counseling pre-operatively. After operation, the satisfaction level was noted before the patients were discharged. In this series only patients between 20-65 years and who had routine operation were included. Routine Counseling: It is usual practice in the hospital that the patients are routinely counseled by the doctor in the unit before operation. This counseling is not standardized but is done by the doctors as they deem fit. Comprehensive Counseling: The basic components of the comprehensive counseling include explaining the nature of operation in simple language, why it is needed; it’s possible complication and outcome of the operations. Results: The present study showed that comprehensive counseling after the routine counseling by the doctors provides a much higher level of satisfaction in the operated patient (P value 0.001). Conclusion: The present study showed that comprehensive counseling on the top of a routine counseling provides a much higher level of satisfaction in the operated patient (P value 0.001) in comparison to routine counseling only. The routine counseling usually is done by a doctor and lacks comprehensiveness possibly because of the time constraints.